(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
Three new species belonging to two genera of Araceae from Bangladesh, namely Alocasia hararganjensis H. Ara & M.A. Hassan, Alocasia salarkhanii H. Ara & M.A. Hassan and Typhonium elatum H. Ara & M.A. Hassan are described and illustrated. Diagnostic morphological characters of each of the new species are provided. A comparative morphological characteristic for each new species with their closest described species has also been provided.